Exploring restoration efforts from a social lens: statistical models reveal relationships between salmon habitat restoration efforts and ecological and social characteristics of the Puget Sound basin, USA - Brittany D King; Robert Fonner (Ecology and Society)
Habitat restoration is an important tool for promoting the conservation and recovery of imperiled species and is motivated by both environmental and social factors. As new restoration efforts are considered, it is important to look back and see what can be learned from past efforts, including how restoration benefits are distributed across communities through an equity lens. Focusing primarily on the Puget Sound basin in the state of Washington, this study investigates correlations between environmental and social factors and the spatial distributions of past restoration efforts. We specified statistical models to explain the variation in the number of restoration worksites undertaken in subwatersheds as a function of environmental and social variables. Using a common set of explanatory variables, we fit four models to examine the distribution of worksites associated with particular types of restoration actions (instream, riparian, land acquisition, and fish passage) and a fifth model to examine the distribution of all aquatic-based restoration worksites across action types. The results reveal statistically significant relationships between the number of worksites and several environmental characteristics, including elevation and species richness number of the Salmon Evolutionary Significant Units. Among the social explanatory variables, the percentage of non-Hispanic white residents in a subwatershed was the most prominent predictor of the number of restoration worksites across models, producing positive and statistically significant estimated coefficients in the instream, riparian, and total worksite models. We also estimated the specified models using data from other populated drainage basins in the region and found corroborating results for some patterns revealed in the Puget Sound basin. Our results provide insight for consideration when planning future restoration effects. With the knowledge of potential past social inequalities and inequities, restoration managers can, moving forward, take appropriate steps to account for these disparities.